2013
DOI: 10.14233/ajchem.2013.13783
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary in vitro Cytotoxic Assay on HepG2 and Antibacterial Screening Activity: Synthesis and Characterization of Organotin(IV) Complexes Derivatives of 2-Methyl-3-nitrobenzoic Acid

Abstract: Three organotin(IV) carboxylate complexes derivatives of 2-methyl-3-nitrobenzoic acid (HL) have been successfully synthesized and characterized quantitatively and qualitatively. The complexes obtained are screened for their preliminary in vitro cytotoxic assay on human liver hepatocellular carcinoma cells (HepG2) and antibacterial screening activity. Results of the infrared and NMR spectroscopy on the acid and complexes showed that the coordination took place via oxygen atoms from the carboxylate anions. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Evidences of the formation of the complexes were further observed in the 13 C-NMR spectra. The 13 C-NMR spectra of complexes 1-2 showed that the d(COO) signals shifted to the downfield region compared to that of the acid, HL indicating the carboxylate anion were bonded to tin(IV) atoms.…”
Section: Characterization By Ftir Spectroscopymentioning
confidence: 79%
See 4 more Smart Citations
“…Evidences of the formation of the complexes were further observed in the 13 C-NMR spectra. The 13 C-NMR spectra of complexes 1-2 showed that the d(COO) signals shifted to the downfield region compared to that of the acid, HL indicating the carboxylate anion were bonded to tin(IV) atoms.…”
Section: Characterization By Ftir Spectroscopymentioning
confidence: 79%
“…The infrared spectra were recorded using a Perkin-Elmer System 2000 FTIR Spectrophotometer as a KBr disc in the frequency range of 4000-400 cm À1 . The spectra for 1 H, 13 C and 119 Sn-NMR were recorded on a Joel JNM-ECX 400 FT-NMR Spectrometer using deuterated d 6 -DMSO as the solvent and tetramethylsilane, TMS as the internal standard.…”
Section: General and Instrumentalmentioning
confidence: 99%
See 3 more Smart Citations